2012
DOI: 10.1016/j.ijms.2011.12.008
|View full text |Cite
|
Sign up to set email alerts
|

The role of lysine ɛ-amine group on the macrocyclization of b ions

Abstract: a b s t r a c tA study was carried out to examine if the amine ( NH 2 ) group located on the side chains of lysine (K), glutamine (Q), or asparagine (N) residue has any effect on the macrocyclization of b ions even though the N-terminals of the peptides were acetylated. The work utilized the model peptides Ac-KYAGFLVG, Ac-QYAGFLV-NH 2 , and Ac-NYAGFLV-NH 2 . The CID mass spectra of b 7 ions originated from these three peptides exhibited that the macrocyclization still occurred for the lysine containing peptide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
(57 reference statements)
1
6
0
Order By: Relevance
“…Upon collisional activation of an ornithine-containing peptide, the amine of the ornithine residue cyclizes via nucleophilic attack at the adjacent carbonyl group, resulting in a characteristic and preferential cleavage C-terminal to the carbonyl group. This phenomenon has been observed before, as lysine and many of its homologues have exhibited similar characteristics as a nucleophile previously [42][43][44][45].…”
Section: Introductionsupporting
confidence: 72%
“…Upon collisional activation of an ornithine-containing peptide, the amine of the ornithine residue cyclizes via nucleophilic attack at the adjacent carbonyl group, resulting in a characteristic and preferential cleavage C-terminal to the carbonyl group. This phenomenon has been observed before, as lysine and many of its homologues have exhibited similar characteristics as a nucleophile previously [42][43][44][45].…”
Section: Introductionsupporting
confidence: 72%
“…Action infrared multi-photon dissociation (IRMPD) spectroscopy, hydrogen/deuterium exchange (HDX), and computational modeling data all support the 5-membered oxazolone ring as the dominant b ion structure, although macrocyclic structures have also been shown to form. [4][5][6][7][8][9][10][11][12][13] These structures have received much interest because ring opening of the macrocycle can lead to scrambling the original peptide sequence. [11,[14][15][16][17] The smallest of the b ions, the b 2 ion, has also been particularly well studied because it can have either a diketopiperazine or oxazolone structure and the preferential formation of one of these structures over the other has been repeatedly shown to be related to amino acid sequence in the first three positions of the peptide.…”
Section: Introductionmentioning
confidence: 99%
“…The m/z 651 ion was observed as the most abundant fragment ion in the CID-MS 4 mass spectrum, and the further isolation (CID-MS 5 ) of the m/z 651 ion have resulted the same CID mass spectra of b 6 ions derived from permuted isomers of YAGFLV-NH 2 , whose CID mass spectra have been reported from our group previously. [36,37] The CID mass spectrum of m/z 668 fragment from b 7 ion of protonated K Ac YAGFLVG and YAGFLV-NH 2 peptides is given in Fig. 2(a).…”
Section: Resultsmentioning
confidence: 99%
“…When the N-terminal of the lysine containing peptide was acetylated, the observation of nondirect fragment ions suggested that lysine ε-amine group could attack to the carbonyl carbon of the oxazolone ring (side-to-tail cyclization) to form macrocyclic structure of b ion. [36] Doubly acetylated peptide, Ac-K Ac YAGFLVG, in which both of the α-amine of the peptide and ε-amine of lysine residue have been acetylated, was also investigated. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%